Vibration assessment of railway viaducts under real traffic using bridge-track models - Rigueiro, Constança (2012)
The main purpose of this work is to evaluate and compare the dynamic response of a ballasted single-span simply supported viaduct using available models for the track system composed by the rails, the sleepers and the ballast. The dynamic response obtained from field measurements is used to establish the dynamic characteristics of the structure and the real traffic response acceleration to be used as reference for the comparisons. For the numeric calculations two types of loading model are considered, namely the moving forces model and the interaction bridge/track/vehicle model.